The Effectiveness of The Form And Method of Giving Solid Organic Fertilizer to The Growth and Yield of Sweet Corn (Zea mays saccharata Sturt) in Inceptisols - Simanihuruk, Bilman Wilman; Anugerah, Ade; Gusmara, Herry (Akta Agrosia, 2021)
This study aims to obtain a combination of organic fertilizers and the method of giving solid organic fertilizer to the growth and yield of sweet corn. The research was conducted from March to May 2019 in Karang Dapo Village, Bingin Kuning District, Lebong Regency, Bengkulu Province. This study used a Complete Randomized Block Design (RCBD) with one factor and three replications, consisting of 11 combinations namely control, solid organic fertilizer (SOF) dose of 2,5 tons ha-1 by localized placement,  5 tons ha-1 by localized placement, Petroganic 500 kg ha-1 by localized placement, Petroganic 1000 kg ha-1 by localized placement, Petroganic 2000 kg ha-1 by localized placement, SOF 2,5 tons ha-1 by side dressing SOF 5 tons ha-1 by side dressing, Petroganic 500 kg ha-1 by side dressing, Petroganic by 1000 kg ha-1 by side dressing, Petroganic 2000 kg ha-1 by side dressing. There were 11 treatment combinations, each treatment was replicated 3 times, so that 33 experimental units were obtained. The results showed that the distribution of SOF 5 tons ha-1 by localized placement had an effect on stem diameter which gave of 3.25 cm, the number of leaves 13.1 strands, and percentage of cob worth selling 100%. Giving SOF 5 tons ha-1 by localized placement giving yields reached 34.4 tons ha-1. Giving organic fertilizer gives better results than without applying organic fertilizer to all observed variables.Keyword: Solid Organic Fertilizer, Petroganic, Sweet corn, localized placement, side dressing